Temporal associations between depressive symptoms, self-esteem, and satisfaction with family life: A 15-year study - Joshanloo, Mohsen (Frontiers in Public Health, 2023)
Introduction In South Korea, depression has significant economic and social impacts, including increased healthcare costs and a relatively high suicide rate. Reducing the prevalence of depressive symptoms in the general population is therefore an important public health goal in this country. To achieve this goal, it is essential to identify the factors that may increase or decrease the risk of depression. This study examined the association between depressive symptoms and two indicators of wellbeing: self-esteem and satisfaction with family life. A primary objective was to examine whether higher self-esteem and satisfaction with family life could predict a decrease in depressive symptoms in the future. Methods A large representative sample was used, collected over a 15-year period with annual lags. The random intercept cross-lagged panel model was used to examine reciprocal associations between the 3 variables at the within-person level. Results All within-person effects were found to be reciprocal, significant, and in the expected direction. Thus, within-person deviations in any of the variables are associated with future within-person deviations in the other variables. Discussion These results suggest that indicators of positive mental health (self-esteem and satisfaction with family life) are protective factors against future depressive symptoms. In addition, depressive symptoms are risk factors for lower self-esteem and lower satisfaction with family life.